Design of level-basin irrigation systems for robust performance - Reddy, Junna Mohan (2011)
Level-basin irrigation is extensively used in South-Western United States where water is very expensive. A well designed level-basin irrigation system is easy to manage, and has significant potential for achieving higher application efficiency and improved salinity control, particularly when the field is laser-leveled. Over the years, three different criteria have evolved to design level-basin irrigation systems: the volume-balance design criterion proposed by the Soil Conservation Service (SCS) of the United States Department of Agriculture (USDA), the limiting length design criterion, and the completion-of-advance criterion. Each one of these three methods has its own advantages and disadvantages. For achieving higher application efficiency, in addition to proper design, a well-defined irrigation scheduling must be followed so that the soil-moisture deficit at the time of irrigation is close to the design depth of the irrigation system. Otherwise, the actual application efficiency will be different (usually lower) than the design application efficiency, and the actual water requirement efficiency achieved may be significantly different (either under-irrigation or over-irrigation) from the design water requirement efficiency. However, if completion-of-advance design criterion is used, the difference between actual and design efficiencies (application efficiency and water requirement efficiency) kept to a minimum. In addition, the actual performance of a level-basin irrigation system designed using the completion-of-advance criterion would be much closer to the design performance even when the inflow flow rate into level-basins fluctuates. This paper will present the results of a simulation study on the robust performance of level-basin irrigation systems designed using the completion-of-advance criterion.